2018
DOI: 10.1002/jcp.26393
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of secreted peptidome from omental adipose tissue in polycystic ovarian syndrome patients

Abstract: Polycystic ovarian syndrome (PCOS) is a common endocrinopathy associated with increased risk of metabolic disorders. Prevalence of adiposity and obesity is greater in women suffering from PCOS. Moreover, adipose tissue dysfunction has been demonstrated in PCOS patients, particularly in abdominal adipose tissue. This dysfunction likely aggravates the metabolic and reproductive abnormalities. We used liquid chromatography-mass spectrometry to compare the peptides secreted from PCOS and non-PCOS abdominal adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The visible blood vessels and connective tissue were removed from the tissue. After rinsed with PBS, the skeletal muscle tissues were cut into small pieces (3–4 mm 3 ) with scissors as described by an established protocol (36, 37). Tissue cutting will lead to release of damaged cells slowly into the medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The visible blood vessels and connective tissue were removed from the tissue. After rinsed with PBS, the skeletal muscle tissues were cut into small pieces (3–4 mm 3 ) with scissors as described by an established protocol (36, 37). Tissue cutting will lead to release of damaged cells slowly into the medium.…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentrations of supernatant from cultured skeletal muscle samples were detected by Bradford method (43) and integrity of these samples were evaluated by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) combined with silver staining. Afterwards the peptides were separated from samples by treatment with Amicon ® Ultra Centrifugal Filters in 10-kDa (Merck Millipore, Billerica, MA, USA) according to the manufacturer's instruction as previously described (37). The “peptidome” present in the filtrates was desalted using a Strata X C18 column (Phenomenex, Torrance, CA, USA) and the desalted peptide solution was vacuum-dried with centrifuges for speed vacuum (SCAN SPEED 40, LaboGene) as previously described (44) and immediately frozen at −80°C until the following processing.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, with the technical development of proteomics and related methodologies, endogenous peptides are going to become a promising research focus, attracting the attention of a large number of researchers. 21 A number of researches have been performed to identify the endogenous peptides which participated in adiposity, 32 preeclampsia, 33 bronchopulmonary dysplasia, 31 polycystic ovarian syndrome 9 and, especially in cancer. 34 These studies further revealed the pathogenesis of corresponding diseases and provided new ideas and choices for the diagnosis and treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide is a type of organic compound produced by endocrine glandular tissues or organs, containing 3-50 amino acids. 9 As an important role, peptide participates in almost all physiological activities, including cell differentiation, immune regulation and, especially, tumor formation. 10 In recent years, the application of peptides in the diagnosis and treatment of BC has aroused increasing interest.…”
Section: Introductionmentioning
confidence: 99%
“…The peptides were extracted and labeled with tandem mass tag (TMT) according to the manufacturer's instructions. 19,20 The labeled samples were analyzed by the Analysis and Testing Center of Nanjing Medical University (http://fxcszx. njmu.edu.cn/).…”
Section: Lc-ms/ms Detectionmentioning
confidence: 99%